PERFORMANCE OF BLENDED SURFACE ACTIVE AGENT WITH POLYMER FOR ENANACED OIL RECOVERY - MOHAMED ABO JABAL, AYMAN ABO EL RHMAN (2012)
Water soluble polymers have been widely used to improve mobility control in Enhanced Oil Recovery (EOR) processes. Partially hydrolyzed polyacrylamide polymer (HPAM), anionic surfactant such as sodium dodecyl sulphate (SDS) blended with polyacrylamide (SDS-b-PAM) and SDS blended with co-polyacrylamide acrylic acid (SDS-b-PAM CO AA) have been investigated and used for polymer flooding processes in this work. Partially hydrolyzed polyacrylamide polymer (HPAM) has been used as an effective viscosifier for flooding processes. Studies have found that HP AM is a good candidate for high temperature condition in the absence of oxygen and divalent ions. The studies found that the PAM started to degrade rapidly associated with the presence of -NH2 in PAM which was hydrolyzed at 65 °C. At this temperature the polymer viscosity reduces abruptly due to mechanical and shears forces. This is accompanied by adverse precipitation due to the interaction between divalent cations (Mg2 + and Ca2 +) with the product of PAM hydrolysis which are thought to be acrylic acids or hydroxides. This is not acceptable for Chemical Enhanced Oil Recovery (CEOR) application where the reservoir temperature exceeds I 00 °C. Additionally at high salinity conditions will lead to an excessive adsorption and retention of polymer in porous medium altering the rheological properties of PAM. Polyacrylamide PAM has been synthesized by free radical polymerization using 5 - 25 (w/v)% acrylamide as monomer, lxl0'3- 5x10-3 (w/v)% potassium persulphate (KPS) as initiator, and 2- 6 (w/v) % urea as a terminating agent in aqueous medium maintained at a pH of 9 - I 0 through the incorporation of sodium dihydrogen phosphate and sodium carbonate. To overcome both premature hydrolysis and susceptibility to precipitation PAM is copolymerized with Acrylic Acid AA.